2012
DOI: 10.1007/s12020-012-9840-7
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-7 expression in tears and orbital tissues of patients with Graves’ ophthalmopathy

Abstract: The aim of this study was to explore whether IL-7 participates in the pathogenesis of Graves' ophthalmopathy (GO). This was a prospective study. 20 GO patients (40 eyes) and 20 healthy volunteers (40 eyes) were recruited. The tear concentration of IL-7 was measured using ELISA assay. IL-7 expression in orbital tissues was evaluated by immunohistochemistry. Patients with inactive GO had the highest IL-7 concentrations in the tears, followed by healthy controls and patients with active GO per ELISA. Immunohistoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 44 publications
0
22
1
Order By: Relevance
“…The reason for increased IL-7 concentration in the inactive phase was unclear, but might have to do with fibroblasts proliferating in the chronic stage. 29 An influence of serum on tear cytokine concentrations was not observable in the serum analysis results.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The reason for increased IL-7 concentration in the inactive phase was unclear, but might have to do with fibroblasts proliferating in the chronic stage. 29 An influence of serum on tear cytokine concentrations was not observable in the serum analysis results.…”
Section: Discussionmentioning
confidence: 85%
“…11,28,29 Tear IL-1b, IL-6, and IL-17A levels were higher as CAS increased, indicating that it may be possible to use these cytokines as markers of disease activity. The results also indicated that Th1 cytokines, Th2 cytokines, and Th17 cytokines were involved in the course of TAO.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, patients with inactive GO were found to have the highest IL-7 concentrations in tears, followed by healthy controls and patients with active GO. Moreover, an immunohistochemical analysis revealed that IL-7 expression in orbital tissues of inactive GO samples was higher than that of a relevant control group [30]. According to the authors, this effect could be explained by proliferation of fibroblasts in chronic stage of ophthalmopathy.…”
Section: Gd-total (N = 37) Gd-active (N = 15) Gd-inactive (N = 8) Gd-mentioning
confidence: 95%
“…All followed patients were diagnosed with GO at the Ophthalmology, Shanghai Gongli Hospital (Shanghai, China), from May 2014 to August 2017, using the Bartley criteria. 2 Routine ophthalmic examinations included ocular surface, visual acuity, the time of tear film break-up, fundus, slit-lamp, fluorescein examinations, and the shimmer experiment was conducted to determine the severity of TAO. 19 The TAO was detected based on previous reports.…”
Section: Subjectsmentioning
confidence: 99%